2014
DOI: 10.3109/14767058.2014.927424
|View full text |Cite
|
Sign up to set email alerts
|

Is there association between ABO blood group and the risk factors of unfavorable outcomes of pregnancy?

Abstract: There are four major blood groups in human based on the presence of A and B antigens. ABO gene encodes A and B antigens on the surface of red blood cells and there are reported relations between this blood phenotype and pregnancy outcomes in the women. In this study, medical records of 792 healthy pregnant women were investigated and their age and blood test results including blood group with fasting blood sugar, hemoglobin, hematocrit, urea, creatinine and red blood cell counts were analyzed in statistical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In a retrospective cohort of 5320 pregnant women who attended a single tertiary care centre in Thailand, ABO blood group was found to be associated with preeclampsia, but not with GDM . A more recent study of 792 healthy Iranian pregnant women observed that women with blood type AB had higher fasting blood glucose in the second trimester than those with blood type A . In a large prospective cohort of Chinese women with detailed longitudinal documentation of confounders, we observed the women with blood group AB were less likely to have a positive GCT and GDM after adjusting for confounders, suggesting that the association between the ABO blood group and the risk of diabetes and GDM may differ by populations.…”
Section: Discussionmentioning
confidence: 55%
“…In a retrospective cohort of 5320 pregnant women who attended a single tertiary care centre in Thailand, ABO blood group was found to be associated with preeclampsia, but not with GDM . A more recent study of 792 healthy Iranian pregnant women observed that women with blood type AB had higher fasting blood glucose in the second trimester than those with blood type A . In a large prospective cohort of Chinese women with detailed longitudinal documentation of confounders, we observed the women with blood group AB were less likely to have a positive GCT and GDM after adjusting for confounders, suggesting that the association between the ABO blood group and the risk of diabetes and GDM may differ by populations.…”
Section: Discussionmentioning
confidence: 55%
“…10 A study consisting of 792 Iranian pregnant women observed that women with blood group AB had higher fasting blood glucose in the second trimester than those with blood group A. 20 But still there are not enough studies in the literature about the association of ABO blood groups with GDM. Because of the increasing prevalence of GDM and DM after GDM, we aimed at investigating any possible relationship between the ABO blood group system and GDM and also transitioning to DM.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the relationship between ABO blood groups and PE which has been observed in many studies for years resulted in conflicting conclusions. 9,10 Adverse pregnancy complications including PE, preterm birth and delivery of low birth weight (LBW) babies represent a major global public health concern. Although these complications generally depend upon the underlying maternal medical conditions such as poorly controlled blood pressure and diabetes, fetal and placental factors can also be responsible from this fetal complication.…”
mentioning
confidence: 99%